An Overview of Recent Advances in Pathogenesis and Diagnosis of Preeclampsia (Iranian Journal of Kidney Diseases, 2012)
Preeclampsia is a serious complication of pregnancy, which is the cause of 60 000 maternal deaths annually worldwide. In addition to the well-known maternal risk factors such as hypertension, diabetes mellitus, antiphospholipid antibody syndrome, obesity, aging, and multiple pregnancies, recent studies have identified the role of genetic and immunological factors in the pathogenesis of preeclampsia. In particular, imbalance between angiogenic and anti-angiogenic factors, anti-angiotensin II type 1 receptor antibodies and dysregulation of oxygen supplies can cause preeclampsia. A group of biomarkers have been introduced for diagnosis of preeclampsia. Chief among them is the ratio of soluble fms-like tyrosine kinase-1 to placental growth factor, which can be used in clinical practice. Recent studies have shown high specificity and sensitivity of these markers for early diagnosis of preeclampsia, which is critical for prevention of fetal and maternal complications.